Machining of Optical Surfaces in Brittle Materials using an Ultra-Precision Machine Tool - Shore, Paul (Cranfield University, 1995)
Investigations of machining optical surfaces into brittle materials using an ultra precision machine tool are presented. The newly developed ultra precision NION machine is evaluated to gain a good appreciation of its operating performance. The machining accuracy capability of this machine is established by careful measurement of its; motion accuracy, thermal and dimensional stability and loop stiffness. Corroboration of these measurements are provided by assessment of surfaces which were produced in soft "easily machined" metal materials. It was found that surfaces smooth to -1 nm Ra could be produced on the NION machine and with a form error of less than 100 nm P-V. The main source of figure error, approximately 80 nm, was found to be caused by the synchronous axial error motion of the workhead spindle. Other elements of the machine, including thermal effects, incurred less than 25 nm of additional figure error. Assessment of the diamond turning process for the producing optical surfaces made in a number of important optical materials, which are ostensibly brittle, were undertaken. Turning tests were carried out to establish the relative difficulty for machining optical surfaces in these materials and to define the most important parameters which affect the attained surface quality. Assessment of the produced surfaces was based on their roughness quality, surface morphology and residual stress condition. It was found that diamond tool edge quality degraded with total cut distance. Tool cut distance was found to be a major influence on achievable material removal rate before micro- fractures became present at the surface. Surface quality and residual stress condition were also greatly influenced by the overall tool cut distance. Diamond grinding trials were also carried out using the NION machine tool. These grinding trials were carried out using a mode of grinding which permits complex shape optical surfaces to be produced. Various grinding technologies were employed to establish the optimum methods. Selected grinding trials were carried out to establish the dominate parameters affecting the optical quality. Assessment of the machined surfaces was in regard of their surface roughness, residual stress and severity of sub-surface micro cracking. It was found that grinding wheel specification was a major influence on surface quality and sub-surface damage. The level of residual stress associated with "ductile" mode grinding was not found to prohibit its application toward the direct manufacture of optical elements. Selection of grinding parameters which ensured the grain depth of cut, GDOC, ., allowed glass surfaces to be parameter did not exceed the materials critical depth, d, ground to 1-2 nm Ra. These ground glass surfaces appeared free of any surface fractures. Sub-surface assessments did however reveal small levels of micro-fractures hidden below the surface. Discussion of both machining processes is provided. Available material removal rates for each process is given when cutting a number of important optical materials. Conclusions regarding the production of both Infrared and visible wavelength optics using the NION machine tool are provided. Recommendations for future work to improve both; the understanding of the processes and the effectiveness of applying the processes are suggested.